Determinant of SMEs Income using Structural Equation Model (SEM) - Anita Handayani; Heri Pratikto; Sudarmiatin Sudarmiatin; Agus Hermawan; Elok Vilantika (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Small and Medium Enterprises (SMEs) are business activities that can be carried out by everyone, as long as that person can manage and develop the business. SMEs also have a role in economic independence, which can later lead to national independence. SMEs in running their business are sure to be pursued is related to income and profits. The purpose of this study was to analyze how the direct effect of length of business and level of education on the income of Furniture SMEs in Menganti, Gresik, and the indirect effect of financial behavior as intervening variables. The study used 155 furniture SMEs in Menganti Gresik with financial behavior as an intervening variable. The exogenous variable uses the length of business and education level, and the endogenous variable is SME income. using Structured Equation Model (SEM). Based on the results of the study, it shows that each variable for its direct effect shows that all variables have an effect on endogenous variables, while for indirect it shows that financial behavior is capable of intervening between business length and income, and education level and income.